2021
DOI: 10.3390/su131810103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Food Security and Agriculture in Iran: A Survey

Abstract: The consequences of COVID-19 on the economy and agriculture have raised many concerns about global food security, especially in developing countries. Given that food security is a critical component that is affected by global crises, beside the limited studies carried out on the macro-impacts of COVID-19 on food security in Iran, this paper is an attempt to address the dynamic impacts of COVID-19 on food security along with economic and environmental challenges in Iran. For this purpose, a survey was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…A qualitative data analysis revealed that similar to elsewhere in the world ( Nchanji et al. , 2021; Rad et al. , 2021; Schmidhuber et al.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…A qualitative data analysis revealed that similar to elsewhere in the world ( Nchanji et al. , 2021; Rad et al. , 2021; Schmidhuber et al.…”
Section: Resultsmentioning
confidence: 82%
“…A qualitative data analysis revealed that similar to elsewhere in the world Rad et al, 2021;Schmidhuber et al, 2020;Workie et al, 2020), COVID-19 caused such disruptions to agricultural activities among Vietnamese farm households via many channels, such as (1) travel restrictions/staying-at-home orders → inability to work on farm → output decline; (2) travel restrictions/staying-at-home orders → lack of/less access input; increased farm production costs → output decline; (3) travel restrictions → higher intermediary transaction costs; more (complicated) regulations → inability to sell outputs due to complicated regulation/unprofitability; (4) travel restrictions → customers paying higher prices → lower demand → inability to sell outputs; (5) strict travel restrictions/staying-athome orders in some hot spots → no allowance to transport outputs → inability to sell outputs; (6) travel restrictions (and closure of borders) → inability to do business with traders, especially foreign traders → inability to sell outputs and (7) demand shocks in urban areas (e.g. customers suffering from income loss, informal traders being not allowed to work or closure of public establishments such as schools and restaurants) → lower demand for agricultural products → inability to sell outputs.…”
Section: Agricultural Disruptions In Covid-19mentioning
confidence: 81%
See 2 more Smart Citations
“…Research shows that the COVID-19 pandemic has affected food security in Iran ( Rad et al, 2021 ) and worldwide ( Niles et al, 2021 , Sereenonchai and Arunrat, 2021 ). Strategy B ( Sustainable food systems ) concentrates on providing a sufficient food supply for the whole population in Iran, aiming at providing access for all people to healthy food and nutrients, which can be achieved by providing the required financial support and subsidies as well as strengthening the food supply chain in this country.…”
Section: Strategy Formulation and Scenario Analysismentioning
confidence: 99%